Dakwah Transformatif Muhammadiyah dalam Mewujudkan Masyarakat Madani melalui Jihad Konstitusi - Hamdanny, Daniel Rusyad (Jurnal Dakwah, 2021)
Muhammadiyah, since its establishment in 1912, has been a pioneer of transformative da'wah in shaping civil society in the archipelago. Various approaches and strategies are taken by Muhammadiyah in response to the challenges of the times and the leadership style of the Organization. Under the leadership of Din Syamsuddin (2005-2015), Muhammadiyah's transformative da'wah was carried out, one of which was through constitutional jihad in an effort to guide and correct the legislative process and products to conform to the morals and ideals of Pancasila and the 1945 Constitution. This paper attempts to describe the da'wah strategy used by Muhammadiyah within the movement from transformative da'wah perspective. The research uses a qualitative approach with the method of discourse analysis on the literature; books, ebooks, news articles, scientific journals, seminar proceedings, audio-visual recordings, interview transcripts, Constitutional Court decisions and other documents deemed credible related to the Muhammadiyah constitutional jihad discourse. Whereas Constitutional Jihad from the perspective of transformative da'wah is pursued through two methods; namely the method of reflection in the form of political ijtihad that seeks to reconcile constitutional norms with Islamic values, as well as the method of action in the pre-legislation process through a research approach (uslubul bahts), in the legislative process through a critical approach and participatory guidance (uslub an naqd wal irsyad) , and post-legislation with a legal monitoring and judicial review approach (uslub al muqarabah wal muraja'ah). Keywords: Muhammadiyah; Transformative Da'wah; Civil Society; Constitutional Jihad Muhammadiyah, sejak pendiriannya pada tahun 1912, telah menjadi pelopor dakwah transformatif dalam membentuk masyarakat madani di tanah air. Berbagai pendekatan dan strategi ditempuh Muhammadiyah mengikuti tantangan zaman dan gaya kepemimpinan Persyarikatan. Di bawah kepemimpinan Din Syamsuddin (2005-2015) dakwah transformatif Muhammadiyah dilakukan salah satunya melalui jihad konstitusi dalam upaya mengawal dan mengoreksi proses dan produk legislasi agar sesuai dengan moral dan cita-cita Pancasila dan UUD 1945. Paper ini mencoba menguraikan strategi dakwah yang digunakan Muhammadiyah pada gerakan tersebut ditinjau dari teori Dakwah Transformatif. Penelitan menggunakan pendekatan kualitatif dengan metode analisis wacana terhadap pustaka; buku, ebook, artikel berita, jurnal ilmiah, prosiding seminar, rekaman audio-visual, transkrip wawancara, putusan Mahkamah Konstitusi dan dokumen lainnya yang dianggap kredibel terkait diskursus jihad konstitusi Muhammadiyah. Bahwa Jihad Konstitusi dari perspektif dakwah transformatif, ditempuh melalui dua metode; yaitu metode refleksi dalam bentuk ijtihad politik yang berupaya merekonsiliasi norma konstitusi dengan nilai-nilai Islam, serta metode aksi pada proses pra-legislasi melalui pendekatan riset (uslubul bahts), pada proses legislasi melalui pendekatan kritis dan bimbingan partisipatif (uslub an naqd wal irsyad), dan pasca legislasi dengan pendekatan monitoring dan pengujian hukum (uslub al muqarabah wal muraja’ah). Kata Kunci: Muhammadiyah; Dakwah Transformatif; Masyarakat Madani; Jihad Konstitusi,